Rural Revitalization from the Perspective of Chinese Modernization: Realistic Dilemmas and Path Construction - Wang, Jing (International Journal of Social Sciences and Public Administration, 2024)
Modernization is an eternal proposition in the process of promoting the great rejuvenation of the Chinese nation, which is related to the destiny and survival and development of the Chinese nation and the Chinese people. In the development process of Chinese-style modernization, the countryside is still a solid foundation for China to achieve the goals of economic development and modernization. To realize the strategy of rural revitalization is the logical base for the overall strategy of Chinese-style modernization. From the holistic perspective to examine the practice of rural revitalization, the comprehensive promotion of rural revitalization is still plagued by inertia of thinking and path dependent, rural governance has shown the value concept, the main body of governance, the division of responsibilities and rights and digital technology and other aspects of the "fragmentation", thus blocking the pace of the comprehensive realization of rural revitalization. Therefore, it is suggested to guide the formation of farmers' values through party building, stimulate the inner power of the countryside through the coordination of multiple subjects, optimize the rural power and responsibility system through the integration of the three governance, and integrate digital resources through the integration platform, so as to realize the rural revitalization from the perspective of Chinese modernization.